Determination of Total Content of Lead, Chromium, and Mercury at Trace Levels in Cement Matrix Using FAAS, GFAAS, and CVAAS: Validation of the Method - Calderón Jiménez, Bryan (2017)
This study shows the validation process for the determination of total trace concentration of lead (Pb), chromium (Cr) and mercury (Hg) in cement matrix using analytical techniques FAAS, GFAAS and CVAAS. The proposed digestion method consisted in a multistage microwave digestion, which showed the capability to dissolve all the sample (0,5 g) in 3,5 h without the presence of particles or remain solid. The linearity of the methods FAAS, GFAAS and CVAAS were corroborated using ordinary least square model (OLS) and using a graphical interpretation of the residuals from the calibration curve. The homoscedasticity of the variance was demonstrated using the Bartlett test. The results show a good agreement and excellent results in terms of linearity of the methods. The sensitivity of the calibration curves remained invariant over the time. The methods showed a small increase of the repeatability and intermediate repeatability comparing with the obtained for aqueous matrix. However, the repeatability components are less than 4 % and 6 %, respectively. The results also showed how the matrix effect, as a source of error in the determination of Cr and Pb by FAAS, was reduced using deuterium lamp as a background correction. The recoveries obtained for FAAS methods were 106.5 % for Pb and 90.5 % for Cr. The Pb and Hg were measured using GFAAS and CVAAS. These methods obtainded a 100% of recovery of the element tested. The LOD obtained in this validation show reach levels of 0.016 mg kg-1 for Cr (FAAS), 0.064 mg kg-1 for Pb (AAS), 8.72 μg kg-1 for Pb (GFAAS) and 0.43 μg kg-1 for Hg (CVAAS). Finally, the uncertainty of these methods had a low impact in the measurement, having in relative terms a level of 3.95 %, 2.28 % y 13.27 % for Pb, Cr and Hg, respectively. It is concluded that these methods show a good performance to measure metals, specifically Pb, Cr and Hg in the cement matrix, if some factors such as proper digestion of the samples and systematic effects correction will be consider.